Magmatic evolution of the Jbel Boho alkaline complex in the Bou Azzer inlier (Anti-Atlas/Morocco) and its relation to REE mineralization - Benaouda, Rachid; Schenk, Volker (Journal of African earth sciences, 2017)
The Jbel Boho complex (Anti-Atlas/Morocco) is an alkaline magmatic complex that was formed during the Precambrian-Cambrian transition, contemporaneous with the lower early Cambrian dolomite sequence. The complex consists of a volcanic sequence comprising basanites, trachyandesites, trachytes and rhyolites that is intruded by a syenitic pluton. Both the volcanic suite and the pluton are cut by later microsyenitic and rhyolitic dykes. Although all Jbel Boho magmas were probably ultimately derived from the same, intraplate or plume-like source, new geochemical evidence supports the concept of a minimum three principal magma generations having formed the complex. Whereas all volcanic rocks (first generation) are LREE enriched and appear to be formed by fractional crystallization of a mantle-derived magma, resulting in strong negative Eu anomalies in the more evolved rocks associated with low Zr/Hf and Nb/Ta values, the younger syenitic pluton displays almost no negative Eu anomaly and very high Zr/Hf and Nb/Ta. The syenite is considered to be formed by a second generation of melt and likely formed through partial melting of underplated mafic rocks. The syenitic pluton consists of two types of syenitic rocks; olivine syenite and quartz syenite. The presence of quartz and a strong positive Pb anomaly in the quartz syenite contrasts strongly with the negative Pb anomaly in the olivine syenite and suggests the latter results from crustal contamination of the former. The late dyke swarm (third generation of melt) comprises microsyenitic and subalkaline rhyolitic compositions. The strong decrease of the alkali elements, Zr/Hf and Nb/Ta and the high SiO2 contents in the rhyolitic dykes might be the result of mineral fractionation and addition of mineralizing fluids, allowing inter-element fractionation of even highly incompatible HFSE due to the presence of fluorine. The occurrence of fluorite in some volcanic rocks and the Ca-REE-F carbonate mineral synchysite in the dykes with very high LREE contents (Ce ∼720 ppm found in one rhyolitic dyke) suggest the fluorine-rich nature of this system and the role played by addition of mineralizing fluids. The REE mineralization expressed as synchysite-(Ce) is detected in a subalkaline rhyolitic dyke (with ΣLREE = 1750 ppm) associated with quartz, chlorite and occasionally with Fe-oxides. The synchysite mineralization is probably the result of REE transport by acidic hydrothermal fluids as chloride complex and their neutralization during fluid-rock interaction. The major tectonic change from compressive to extensional regime in the late Neoproterozoic induced the emplacement of voluminous volcaniclastic series of the Ediacran Ouarzazate Group. The alkaline, within-plate nature of the Jbel Boho igneous complex implies that this extensional setting continued during the early Cambrian.
Gesehen am 03.04.2018